The repeated evolution of stripe patterns is correlated with body morphology in the adaptive radiations of East African cichlid fishes. Issue 2 (7th February 2022) - Urban, Sabine; Gerwin, Jan; Hulsey, C. Darrin; Meyer, Axel; Kratochwil, Claudius F.
Abstract: Color patterns are often linked to the behavioral and morphological characteristics of an animal, contributing to the effectiveness of such patterns as antipredatory strategies. Species‐rich adaptive radiations, such as the freshwater fish family Cichlidae, provide an exciting opportunity to study trait correlations at a macroevolutionary scale. Cichlids are also well known for their diversity and repeated evolution of color patterns and body morphology. To study the evolutionary dynamics between color patterns and body morphology, we used an extensive dataset of 461 species. A phylogenetic supertree of these species shows that stripe patterns evolved ~70 times independently and were lost again ~30 times. Moreover, stripe patterns show strong signs of correlated evolution with body elongation, suggesting that the stripes' effectiveness as antipredatory strategy might differ depending on the body shape. Using pedigree‐based analyses, we show that stripes and body elongation segregate independently, indicating that the two traits are not genetically linked. Their correlation in nature is therefore likely maintained by correlational selection. Lastly, by performing a mate preference assay using a striped CRISPR‐Cas9 mutant of a nonstriped species, we show that females do not differentiate between striped CRISPR mutant males and nonstriped wild‐type males, suggesting that these patterns might be less important for species recognition and mate choice. In summary, our study suggests that the massive rates of repeated evolution of stripe patterns are shaped by correlational selection with body elongation, but not by sexual selection. Abstract : Across the ~1200 cichlid species of the East African rift lakes, melanic horizontal stripes have evolved numerous times. By applying comparative analyses, hybrid crosses, and a behavioral experiment using a CRISPR/Cas9 knockout mutant, our study aims at understanding the ecological function of these horizontal stripe patterns. We suggest that the massive rates of repeated evolution of stripe patterns are shaped by correlational selection with body elongation, but not by sexual selection.